Translational Inhibition of Slug by Pdcd4 Contributes to Invasion Inhibition in Colorectal Cancer Cells - Qing Wang; Wei He; Shilong Han; Maoquan Li; Yanlei Wang; Yekaterina Zaytseva; Li Chen; Jiang Zhu; Hsin‐Sheng Yang (Cancer Medicine)
ABSTRACT Background Colorectal cancer (CRC) metastasis remains a major cause of mortality, driven by epithelial‐to‐mesenchymal transition (EMT) and invasion. Programmed cell death 4 (Pdcd4), a tumor suppressor, is known to inhibit translation via interaction with eukaryotic initiation factor 4A (eIF4A). Previous studies have established that Pdcd4 suppresses stress‐activated protein kinase 1‐interacting protein 1 (Sin1) translation through the mTORC2‐Akt axis, thereby downregulating Snail expression and EMT in CRC cells. However, whether Pdcd4 directly regulates Slug, another critical EMT transcription factor, remains unexplored. Method PDCD4 shRNA and SLUG siRNA were used to knock down Pdcd4 and Slug in colorectal cancer cells, respectively. The sucrose gradient fractionation was performed to determine SLUG translation. A luciferase reporter assay was used to determine the role of the SLUG 5′ untranslated region (5'UTR) on Pdcd4 inhibition. The effect of Slug on promoting invasion was determined by Matrigel invasion assays. Result Knockdown of Pdcd4 in colorectal cancer cells increased Slug protein levels without altering SLUG mRNA abundance. Sucrose gradient fractionation revealed that Pdcd4 knockdown elevated the proportion of SLUG mRNA in polysome fractions, demonstrating Pdcd4‐mediated suppression of SLUG translation. To validate the mechanism, the SLUG 5′UTR was cloned and fused to a luciferase reporter and named SLUG‐5′UTR‐Luc. Pdcd4 knockdown markedly enhanced SLUG‐5′UTR‐Luc activity; whereas, ectopic Pdcd4 expression suppressed it, indicating that the SLUG 5′UTR is critical for Pdcd4‐mediated translational repression. Treatment with the eIF4A inhibitor silvestrol substantially reduced Slug protein levels and SLUG‐5′UTR‐Luc activity. In addition, Pdcd4 overexpression decreased Slug protein abundance and restored E‐cadherin expression. Notably, Slug knockdown in Pdcd4‐deficient cells rescued E‐cadherin expression and abrogated the invasive phenotype. These findings suggest that up‐regulation of Slug translation by Pdcd4 knockdown contributes to enhanced invasion. Conclusion Pdcd4 suppresses colorectal cancer invasion by translationally downregulating Slug expression.